Peranan KKN Tematik Sebagai Potensi Untuk Memulihkan Ekonomi di Desa Sindangmekar - Yogaswara, Dendi; Ramdani, Hadi Sa’ban; Chaerunisa, Adinda; Putra, Aditia Pratama; Faujiah, Aeni; Ramadhana, Alfin; Muspiana, Ana; Rahayu, Asri Nurjati; Taofik, Fahmi Moh.; Gumilar, Febri; Gumilar, Gugum Rahmat; Jami, Hikmatu; Khoer, Miftahul; Ilmayasa, Muhammad Qalam; Nuraeni, Noni; Lestari, Putri Zakiyah; Nugeraha, Reksya Adi; Riyanto, Rival; Siswanti, Siswanti; Hamidah, Ucu Siti; Fathir, Mirza (Jurnal PkM MIFTEK, 2022)
Real Work Lecture (KKN) is a form of application of knowledge that has been obtained during lectures that is applied in social life. The KKN which was carried out in Sindangmekar Village, Wanaraja District, Garut Regency, West Java lasted for 1 month starting from August 1 to August 31 2022. Sindangmekar Village was the village chosen as the destination for the implementation of KKN by Group 7. The potential of the existing villages Most of them are in agriculture, where this is one of the livelihoods for the community. This is because agricultural land in Sindangmekar Village is more suitable for use in rainfed agriculture, where the agriculture relies on rainwater so that the type of plant that is widely cultivated is corn which is used as a livelihood for the surrounding community. But not only in the agricultural sector, the potential that exists in Sindangmekar Village is also in the textile sector, namely MSMEs that produce Muslim Clothing & Veils. KKN begins with the village observation process and sees the potential of the village which will be the main target in the implementation of KKN. The implementation of the KKN program is carried out in a balanced manner starting with planning, implementation, and evaluation. The results achieved from the entire KKN work program include developing community skills and helping in human resource development to increase the potential of the local village. As well as developing concepts in the processing and utilization of corncob waste for the community and students. Briefing on the importance of protecting the environment to avoid waste. And planting 1000 plant seeds as a form of greening activities.